Feasibility of Cervical Epidural Anesthesia for Breast Cancer Surgery - Manuel Wenk; Christina Massoth; Daniel M. Pöpping; Michael Möllmann (Anesthesiology Research and Practice)
Background. Effects of perioperative cervical level neuraxial blocks on the dissemination of cancer metastases have become a matter of substantial interest. However, experience with these catheters has been limited and data on feasibility and efficacy is sparse. Methods. Data from 39 patients scheduled to undergo breast cancer surgery while awake with a cervical epidural alone was retrospectively analyzed. Results. In 26 patients (66,7%, 95% CI 51,7–81,7) the cervical epidural catheter was sufficient for surgery. In one patient (2.6%, 95% CI 0–7.6) identification of the epidural space was not possible. Four patients (10.3%, 95% CI 0,7–19,9) had an insufficient sensory block. Seven patients (17.9%, 95% CI 5,7–30,1) had a partially insufficient sensory block. Rates of failed epidural blocks were not significantly different between different insertion levels. 21 patients (80.8%, 95% CI 65,4–96,1) developed hypotension and required an intravenous vasopressor. One patient developed nausea. In one patient the dura was accidentally punctured. No neurological damage was observed. No other major complications were observed. Discussion. Epidural punctures in the cervical region are feasible but do bear potential for major complications. Anesthesiologists should familiarize themselves with high epidural block techniques.